Interest in tanning beds and sunscreen in German-speaking countries - Kirchberger, Michael Constantin; Reinhard, Raphael (Journal der Deutschen Dermatologischen Gesellschaft, 2017)
Background The growing incidence of nearly all types of skin cancer can be attributed to increased exposure to natural or artificial ultraviolet (UV) radiation. However, there is a scarcity of statistical data on risk behavior or sunscreen use, which would be important for any prevention efforts. Methods Using the search engine Google®, we analyzed search patterns for the terms Solarium (tanning bed), Sonnencreme (sunscreen), and Sonnenschutz (sun protection) in Germany, Austria, and Switzerland between 2004 and 2016, and compared it to search patterns worldwide. For this purpose, “normalized search volumes” (NSVs) were calculated for the various search queries. The corresponding polynomial functions were then compared with each other over the course of time. Results Since 2001, there has been a marked worldwide decrease in the search queries for tanning bed, whereas those for sunscreen have steadily increased. In German-speaking countries, on the other hand, there have - for years - consistently been more search queries for tanning bed than for sunscreen. There is an annual periodicity of the queries, with the highest NSVs for tanning bed between March and May and those for sunscreen in the summer months around June. In Germany, the city-states of Hamburg and Berlin have particularly high NSVs for tanning bed. Conclusions Compared to the rest of the world, German-speaking countries show a strikingly unfavorable search pattern. There is still great need for education and prevention with respect to sunscreen use and avoidance of artificial UV exposure.
Gesehen am 27.09.2018